Global Unions: Past Efforts and Future Prospects - Fairbrother, Peter; Hammer, Nikolaus (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2005)
International trade unionism faces a major challenge. Historically, Global Union Federations have been small and relatively remote international union secretariats with limited capacity to mobilize and speak on behalf of local members. However, with the changing architecture of international capital and nation states, these union bodies have started to renew themselves. The argument is that the emergent political economy provides the base upon which these unions can begin to campaign and represent members in more dynamic ways than in the past. Critical to these developments has been the promulgation of International Framework Agreements which adapt and extend familiar tools of representation. The outcome is the possibility of a multi-faceted form of trade unionism.